Transformasi Kompetensi Internal Perawat : Peran Spiritualitas dalam Mengurangi Burnout Melalui Self Leadership dan Kecerdasan Emosional - Lady Galatia Lapian (Pusat riset dan Inovasi Nasional, 2025)
Burnout is a critical issue affecting nurses' performance and service quality, especially under high work pressure in hospital settings. This study aimed to analyze the influence of spirituality on nurse burnout, focusing on the mediating roles of self-leadership and emotional intelligence. The research applied a quasi-experimental design with a pretest-posttest non-random control group. A total of 159 nurses were selected via total sampling from RSUD Noongan and RSU GMIM Bethesda. Measurement tools included burnout (MBI), spirituality, self-leadership, and emotional intelligence questionnaires. Data were analyzed using SPSS and Smart-PLS. The results showed a significant negative effect of spirituality on burnout, with self-leadership and emotional intelligence acting as reinforcing mediators. This study concludes that strengthening nurses' spirituality can serve as an internal competence to protect against burnout.